International Trade in Grains: Projections and United States Policy - Sandberg, Lars G. (The Review of Economics and Statistics, 1966)
T HE purpose of this paper is to use estimates of likely developments on the world grain market by 1970 and 1975 to reach sensible policy conclusions with regard to United States grain trade and aid. The estimating methods employed are simple and unsophisticated, largely because of the uncertain nature of the underlying data used. Projections of supply and demand as well as estimates of price elasticities are all subject to considerable error. Use of these data introduces a good deal of uncertainty into the results derived, an uncertainty that increases with each successive calculation. Nevertheless, studies of this kind are valuable for at least two reasons. First, policy decisions have to be made and the results are likely to be improved if the relevant questions have at least been asked, even if the answers are only approximations. This is certainly true in cases like the present one where the general direction of the answers is clear. Secondly, this type of work provides a framework into which better projections and other data can be fitted;as they become available to yield more accurate results and, quite possibly, better policy decisions.